Influence of manufacturing quality of laminated core on a turbogenerator exploitation term - Shevchenko, V.V. (Електротехніка і електромеханіка, 2016)
The problem of calculating the flexural deformation of the laminated core of the stator turbogenerator is examined. The evaluation of the effect of gluing the core sheets on its bending stiffness based on the compliance of the insulating cover sheet of active steel. An impact of pressing effort on the relative movement of the package of sheets is determined. An effect of wear of the insulating layer between sheets of laminated core on its reliability is determined. Conclusions are drawn on how to determine the possibility of extending the life of turbogenerators on the basis of the data obtained Рассмотрен расчет изгибной деформации шихтованного сердечника статора турбогенератора. Выполнена оценка влияния склейки листов сердечника на его изгибную жесткость с учетом податливости изоляционного покрытия листов активной стали, значения усилия прессовки пакета на относительное перемещение листов. Определено влияние износа изоляционного слоя между листами шихтованного сердечника на его надежность. Сделаны выводы, как на основании полученных данных установить возможность продления срока эксплуатации турбогенераторов.